Estetika Sema Dalam Tarekat Sufi Naqsybandi Haqqani Jakarta Sebagai Media Penanaman Pendidikan Tauhid - Agung Dwi Putra (Gondang: Jurnal Seni dan Budaya, 2017)
The concept of beauty (aesthetic) as a central issue to reveal the meaningfulness of the value of a form of art or artwork, can not be done by generalizing. The emergence of the phenomenon of art with the term Sema in the Sufi order Naqsybandi Haqqani Jakarta can certainly be assumed as a transformation of the values of Tauhid education based on the aesthetic concept of Sufism in the domain of Islam, because the existence of Sufi orders in general only offer spiritual teachings (aims) to achieve purification of Tawheed. This research is included in qualitative paradigm with phenomenology approach. Through this research it is revealed that the love of divinity or platonic love based on Tawheed (esoteric) is the aesthetic concept of the Naqsybandi Sema tariqa Haqqani Jakarta as the manifestation of the consciousness of the perpetrators, which is awakened through spiritual training in the tarekat. Sema in the Naqsybandi Haqqani Order of Jakarta is also known to play the role of educational media in instilling the values of Tawheed through its beautiful symbols (exoteric) and meaningful Ketauhidan.